Myrtenol Protects Against Acute Kidney Injury Induced by Cisplatin in Mice - Morteza Amirteimoury; Iman Fatemi* (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Cisplatin is an effective anticancer drug which has some side effects such as acute kidney injury. Myrtenol, a monoterpene alcohol which is found in some plants, has various pharmacological effects including anti-inflammatory and antioxidant activities. In this study, we evaluated the nephroprotective effects of myrtenol in acute kidney injury induced by cisplatin in male mice. Methods: In this experimental in-vivo study, 35 male mice were randomly separated into 5 groups, including control, CIS (20 mg/kg cisplatin, intraperitoneally on day 1), dimethyl sulfoxide (DMSO; received cisplatin only on day 1, plus DMSO 1% on the first day, continued for 3 days), and treatment groups (received cisplatin only on day 1, plus myrtenol 25 mg/kg and 50 mg/kg intraperitoneally on the first day, continued for 3 days). The blood urea nitrogen (BUN) levels were evaluated in serum. The renal tissues were collected for evaluating malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT) activities; histopathological investigation was also performed. Results: Our results showed that cisplatin administration caused significant elevation in the levels of renal MDA and serum BUN; in contrast, renal SOD and CAT activities significantly reduced. Myrtenol treatment, especially 50 mg/kg for four consecutive days mitigated these alternations in serum and renal tissue. Also, the kidney's histopathological investigations were consistent with biochemical and oxidative parameters. Conclusion: The results of our study revealed that myrtenol ameliorates acute kidney injury induced by cisplatin via oxidative stress suppression.